Terahertz exposure enhances neuronal synaptic transmission and oligodendrocyte differentiation in vitro - Xianghui Zhao (Elsevier, 2021)
Summary: Terahertz (THz) frequency occupies a large portion of the electromagnetic spectrum that is between the infrared and microwave regions. Recent advances in THz application have stimulated interests regarding the biological effects within this frequency range. In the current study, we report that irradiation with a single-frequency THz laser on mice cortical neuron cultures increases excitatory synaptic transmission and neuronal firing activities. Microarray assay reveals gene expression dynamics after THz exposure, which is consistent with morphology and electrophysiology results. Besides, certain schedule of THz irradiation inhibits the proliferation of oligodendrocyte precursor cells (OPCs) and promotes OPC differentiation. Of note, the myelination process is enhanced after THz exposure. In summary, our observations suggest that THz irradiation can modulate the functions of different neuronal cells, with different sensitivity to THz. These results provide important understanding of the mechanisms that govern THz interactions with nervous systems and suggest THz wave as a new strategy for neuromodulation.